Retinal and Cortical Contributions to Phosphenes During Transcranial Electrical Current Stimulation. Issue 2 (13th January 2021) - Evans, Ian D.; Palmisano, Stephen; Croft, Rodney J.
Abstract : It is generally believed that the phosphenes induced by transcranial electric current stimulation (tECS) are a product of retinal activation, even when electrode placement is directly over the primary visual cortex. However, the origins of these tECS‐induced phosphenes have not yet been conclusively determined. In this study, phosphene detection thresholds using an FPz‐Oz montage were compared with those from (i) an Oz‐Cz montage to determine whether prefrontal regions, such as the retina, contribute to phosphenes and (ii) an FPz‐Cz montage to determine whether the visual cortex in the occipital lobe contributes to phosphenes. Twenty‐two participants received transcranial current stimulation with each of these montages (as well as a T3‐T4 montage included for exploratory purposes) at 6, 10, 16, 20, 24, 28, and 32 Hz. To estimate differences in current density at the retina and occipital lobe across montages, modeling of current density at phosphene thresholds was measured across 20 head models. Consistent with the proposal that tECS‐induced phosphenes are generated in the retina, increasing current density near the retina (FPz‐Oz relative to Oz‐Cz montage) reduced phosphene thresholds. However, increasing current density near the occipital cortex (FPz‐Oz relative to FPz‐Cz montage) also reduced phosphene thresholds while also requiring less current density at the retina according to the modeling estimates. This suggests that tECS of this occipital cortex also contributed to phosphene perception. © 2020 Bioelectromagnetics Society.